SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENDAFTARAN VENDOR MENGGUNAKAN METODE SMART - Lapu Tombilayuk; Zaini Zaini; Brilian Tri Wuriandhika (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan)
The vendor registration process at PT Badak NGL is still in a manual form, so that it is considered to be less relevant, at the time of vendor registration there is a process of determining the risk classification of the fields determined through the K3L2M questionnaire (Safety, Occupational Health, Environmental Protection and Quality) or CSMS Questionnaire (Contractor Safety Health Environment & Quality (SHEQ) Management Evaluation System). In line with the development of technology to improve the quality of the company, the researcher conducted a study with the title Decision Support System Vendor Registration Selection Using Web-Based SMART Method (Case Study of PT Badak NGL). In designing this system, the system uses SMART (Simple Multi Attribute Rating Technique) method and the development of a structured system applies SDLC (System Development Life Cycle) using the waterfall model with the PHP programming language and the My SQL database. The results show vendor selection based on the classification of risk fields, all test using Black Box function properly